Simulated Lightning in a Convection Permitting Global Model. Issue 17 (12th September 2018) - Field, P. R.; Roberts, M. J.; Wilkinson, J. M.
Abstract: High‐resolution (grid spacing 10 km in midlatitudes) model simulations using explicitly resolved convection in the Met Office Unified Model, as part of the Horizon 2020 PRIMAVERA project, are used to provide a global lightning climatology. The results show for the first time that global simulations can capture the strong diurnal flash rate variation as well as the seasonal variation. The lightning parametrization uses information about the graupel and ice water path to estimate a total lightning flash rate. Comparisons are made with the World Lightning Location Network (that mainly detects cloud to ground lightning) and combined Lightning Imaging Sensor and Optical Transients Detector data set (that provides an estimate of total flash rate). The model results generally capture the temporal behavior and spatial distribution of the lightning over land. Over the ocean, the lightning in the Intertropical Convergence Zone appears excessive. Plain Language Summary: We use a high‐resolution global model that explicitly resolves convection to predict lightning flash rate. The representation of lightning in the model depends upon the upward flux of ice and the amounts of graupel present in the cloud. The model is able to capture the strong diurnal behavior of the lightning activity with the greatest flash rates in the local afternoon. The spatial and seasonal patterns of lightning agree well with two independent observational data sets. Key Points: Global model captures diurnal phase of lightning Spatial and seasonal distributions of lightning compare favorably to two observed data sets The global model has excessive lightning over the tropical oceans